Fracture Dislocation of Shoulder - Manandhar, Hemanta Kumar; Devkota, Pramod; Khadka, Padam Bahadur; Randey, Chakra Raj (Nepal Orthopaedic Association Journal, 2014)
Simultaneous dislocation of shoulder with fracture of the ipsilateral humerus is extremely rare and very little reported in the literature. We report a case of forty three year old man who got right shoulder dislocation with proximal humerus fracture. The patient was treated with open reduction and internal fixation by three 4.5mm screws. The operation went uneventful and has good range of motion of the shoulder after six months of follow up. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9529 NOAJ July-December 2013, Vol 3, Issue 2, 44-45